ANALYSIS OF FACTORS THAT INFLUENCE PEOPLE PAYING ZAKAT WITH THE "CINTA ZAKAT" APPLICATION - Fadhilah, Rafif Aufa; Rabbani, Fawwaz Zaki; Ramadani, Anni Fitri; Tsaqib, Hilya Najmi; Legowati, Diah Ayu (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: In technological progress in the industrial era 4.0, a lot of things in life have been digitized, including zakat payment methods. In this research, we discuss people's interest in paying zakat using the "cinta zakat" application from BAZNAS. The model we use in this research is the technology acceptance model, which is the most relevant in predicting desire and readiness to adopt a technology. This research can help readers increase their understanding of zakat and the use of financial technology to make zakat easier. Method: This research uses a quantitative research model by distributing questionnaires to all Indonesian people who have used the "cinta zakat" application, this questionnaire uses gform and is distributed via social media such as Instagram, WhatsApp, and Facebook. Results: Based on this research in accordance with the technology acceptance model framework such as a. Perceived Usefulness, behavior intention, attitude toward, and actual system to use, society has a positive correlation regarding the use of the "cinta zakat" application in making zakat payments. Novelty: In technological progress in the industrial era 4.0, a lot of things in life have been digitized, including zakat payment methods. This research can help readers increase their understanding of zakat and the use of financial technology to make zakat easier.